Bacillus strains immobilized in alginate macrobeads enhance drought stress adaptation of Guinea grass (2021)
Drought stress reduces crop growth and yield. This study aimed to formulate alginate macrobeads inoculants using strains Bacillus sp. XT13 and XT14, and evaluate their effect on the stress response of guinea grass under drought. First, we produced two prototypes per bacterial strain based on the alginate-bacterial broth ratio and selected one for each strain based on the release kinetics and the biodegradability of the formulates in soil. Then, we evaluated their effect on some biochemical, morphological, and nutritional responses of Guinea grass under drought in greenhouse conditions. The results showed a biodegradability increase and a slow-release rate for the prototypes 70:30 XT13 and 80:20 XT14. The greenhouse experiments showed that inoculation of both Bacillus sp. strains improved plant growth significantly under drought. Furthermore, the co-inoculation of the alginate macrobeads of both strains showed a greater effect on the grass response than that observed with individual inoculations (p < 0.05). When compared with the drought control treatment, the co-inoculation increased plant total dry biomass production by 94.4% and nutritional quality parameters such as crude protein content (260%) and digestibility (10.73%). Co-inoculation also showed a significant effect (p < 0.05) in the plant's antioxidant response, as the ascorbate peroxidase activity decreased 5.46%. In contrast, proline accumulation increased in plants inoculated with the alginate macrobeads of XT13, XT14 and XT13 + XT14 by 3.1-fold, 3.3-fold and 2.3, respectively. Overall, our results suggest that formulation of macrobeads with these bacteria can modulate plants response to drought and have the potential to be a climate change adaptation strategy for agricultural production.